A novel Differential Susceptibility framework for the study of nightmares: Evidence for trait sensory processing sensitivity. (December 2017) - Carr, Michelle; Nielsen, Tore
Abstract: Research on nightmares has largely focused on the nightmare itself and its associated negative consequences, framing nightmare sufferers as victims of a diathesis-stress induced form of psychopathology. However, there is evidence that frequent nightmare recallers are sensitive to a wide range of sensory and emotional experiences, and report vivid, bizarre and even intensely positive dream and daydream experiences. We propose sensory processing sensitivity as a novel trait marker that underlies the unique symptoms and imaginative richness found in nightmare-prone individuals. Sensory processing sensitivity describes an increased emotional reactivity, greater depth of processing, and subtle awareness of environmental stimuli—it is a 'for better and for worse' trait that is associated with positive outcomes in conditions of support, but also confers a tendency to be easily overwhelmed by stressors and adversity. This novel approach places nightmare-prone individuals within the broader framework of Differential Susceptibility and raises the possibility that they may benefit especially from supportive environments—a possibility that is particularly relevant for developing future treatment approaches. Highlights: A novel Differential Susceptibility framework for nightmares is proposed. Sensory processing sensitivity may be a trait marker of nightmare sufferers (NMS). NMS experience maladaptive outcomes to stress, e.g. nightmares and distress. NMS experience adaptive outcomes to positive contexts, e.g. empathy and creativity. NMS may benefit from positive psychology, mindfulness, and social support.